Computation and Estimation of Rainfall Energy and Erosion Indices in Metric Units - Das, D. C.; Babu, Ram (Indian Forester, 1979)
The procedure for computation of erosion indesx values (EI) in metric units and also to convert the EI values already available in FPS units has been discussed. The feasibility of estimating rainfall energy from rainfall amount and EI values from the product of rainfall amount and maximum intensity for a selected duration, need to be explored at a number of locations.